Transmorfofonologisasi suprafiks: dialek Patani merentasi zaman (Jurnal Bahasa, 2005)
It has been observed that in the phonological development of a particular language, the distinctive features of some sounds has gone through some changes; either resulting in additions or vice-versa. This has resulted in some phonemes, which, in the beginning are different, but through this process, have become almost identical, resulting eventually in the existence of a group of words that are pronounced in the same way. Those words are later classified as homonyms. In order to avoid such words from being pronounced the same way (and to retain its distinctive meaning), transfonologisation correlating to the existence of new phonemes has surfaced to facilitate in differentiating the meaning of words. This phenomenon is found in the Pattani Malay dialect whose geographical linguistics overlap with that of the Thai language, which is regarded as the language suprastratum in southern Thailand. To show the changes in such sounds, this paper attempts to discuss, as its premise, the re-formation of a new morphophonological system in Pattani Malay dialect which is the result of the change in suprafix element of long consonant analogous to falling tone phonemes in the Thai language and this is seen as being more relevant in the formation of that particular morphophonological system in lieu of specific needs in new word formation and the need to retain its original meanings.